2020
DOI: 10.3389/fchem.2020.00722
|View full text |Cite
|
Sign up to set email alerts
|

Weyl Fermions in VI3 Monolayer

Abstract: We report the presence of a Weyl fermion in VI 3 monolayer. The material shows a sandwich-like hexagonal structure and stable phonon spectrum. It has a half-metal band structure, where only the bands in one spin channel cross the Fermi level. There are three pairs of Weyl points slightly below the Fermi level in spin-up channel. The Weyl points show a clean band structure and are characterized by clear Fermi arcs edge state. The effects of spin-orbit coupling, electron correlation, and lattice strain on the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Particularly, around this isolated nodal point, the quasiparticle acts similarly to the behavior of Weyl fermions, which are particles of considerable interest in high-energy physics. We summarize some recent studies on Weyl materials as follows: (i) Zhao and Ma (2020) stated that hexagonal MnO ferromagnet is a magnetic Weyl semimetal with spin-gapless state; (ii) Meng W. et al (2020b) predicted that HfCuP compound is a newly designed Weyl semimetal with different types of Weyl nodes; and (iii) Jia et al (2020) reported that the VI 3 monolayer hosts a Weyl fermion and 100% spin-polarization. Furthermore, under the protection from certain crystalline symmetries, two Weyl points of opposite chirality can be stable at the same point, forming a Dirac point.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Particularly, around this isolated nodal point, the quasiparticle acts similarly to the behavior of Weyl fermions, which are particles of considerable interest in high-energy physics. We summarize some recent studies on Weyl materials as follows: (i) Zhao and Ma (2020) stated that hexagonal MnO ferromagnet is a magnetic Weyl semimetal with spin-gapless state; (ii) Meng W. et al (2020b) predicted that HfCuP compound is a newly designed Weyl semimetal with different types of Weyl nodes; and (iii) Jia et al (2020) reported that the VI 3 monolayer hosts a Weyl fermion and 100% spin-polarization. Furthermore, under the protection from certain crystalline symmetries, two Weyl points of opposite chirality can be stable at the same point, forming a Dirac point.…”
Section: Introductionmentioning
confidence: 98%
“…The dimensionality of band-crossings is a criterion used to classify topological semimetals/metals. The most famous topological semimetals/metals with zero-dimensional band-crossings, i.e., zero-dimensional nodal points, are Dirac semimetals/metals (Chen et al, 2015(Chen et al, , 2020Bradlyn et al, 2017;Zhong et al, 2017;Jing and Heine, 2018;Liu et al, 2018b;Zhang et al, 2018b;Khoury et al, 2019;Wang et al, 2020f;Xu et al, 2020) and Weyl semimetals/metals (Peng et al, 2016;Lin et al, 2017;Fu et al, 2018;Zhang et al, 2018c;Zhou et al, 2019;Gupta et al, 2020;Jia et al, 2020;Liu et al, 2020;Meng L. et al, 2020;Zhao B. et al, 2020). We selected Weyl semimetals/metals as examples here because there exists a band-crossing of the valance band and conduction band at an isolated nodal point in the momentum space of these solids.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the DOS peaks of V orbitals are pushed away from the Fermi level, resulting in the enhanced magnetic moment of 1.1 per V ion. A remarkable emerging feature is the band crossing at the M point by two spin up single bands at the energy of eV as highlighted by the green circle in Figure 1 c. Some of the previous works have named such crossings in 2D systems as Weyl points [ 36 , 37 , 38 ], even though the Weyl point was originally defined in three-dimensional materials [ 39 ]. In this work, following previous works, we hereafter call this band crossing as the Weyl point.…”
Section: Resultsmentioning
confidence: 99%
“…[33,34] To date, the Weyl states in most of reported 2D half-metals may belong to type I. The novel type-II Weyl fermions are found in only a few half-metal compounds, including Cr 2 C, [20] VI 3 , [35] and CrN [30] monolayers (MLs). However, they are all hypothetical structures and have not yet been synthesized experimentally.…”
Section: Introductionmentioning
confidence: 99%